Data, discourse, and development: Building a sustainable world through education and science communication - Gibson, Heidi; Short, Mary E.; O'Donnell, Carol (Frontiers in Communication, 2023)
Dramatic expansion of distance learning during COVID-19 widened the digital divide and highlighted the importance of students’ digital and data literacy skills. Simultaneously, science was playing out in front of the public as information and communications about the importance of COVID-19 protective behaviors and vaccines evolved. Yet within the global discourse, misinformation was rampant. The public questioned the validity of COVID-19 data. They did not know who or what to trust. Their concerns about the impacts of COVID-19 protective behaviors and the need for vaccinations rose. Some science educators were asked to avoid discussing the topic with their students. All of this is emblematic of an even larger problem–the inability of many people to understand and use data to make informed decisions to develop their communities. This article will use one example from the Smithsonian Science for Global Goals project: Vaccines! How can we use science to help our community make decisions about vaccines?, which invites students ages 8-17 to use data to change discourse and develop their own communities using content from the SDGs. This project encourages students to: (1) use investigations to gather and analyze data from their communities as they build data literacy skills (data); (2) communicate this information to others as a way of catalyzing and changing community conversations to make informed decisions (discourse); and (3) become active partners in creating more sustainable and equitable communities (development). These competencies of data, discourse, and development—integrated into science, technology, engineering, and math education for sustainable development (STEM4SD)—are aligned with a ‘data for learning’ conversation that emerged during the pandemic. To expand students’ data skills, educators must be grounded in a framework that holistically considers ethics, community impact, and science. Data must be contextualized to the problems that students face locally. Students must be given the tools to communicate scientific understanding to others in service of sustainable development. As such, an SDG-aligned approach to data for learning that promotes discourse, while educating students on the underlying science and social science of sustainable development, drives learners to act to protect themselves, our societies, and our planet.